Transnational feminism and global advocacy in South Asia - Gita Rajan, 1952-; Desai, Jigna (London : Routledge, 2013)
Transnational feminism has been critical to feminist theorizing in the global North over the last few decades. Perhaps due to its broad terminology, transnational feminism can become vague and dislocated, losing its ability to name specific critiques of and responses to empire, race, and globalization that are emboldened by its transnational remit. This volume encompasses an expansive engagement and exploration of transnational South Asian feminist movements, networks, and critiques within the context of the popular and the diaspora in South Asia. The contributing authors address key issues in a global context, especially as they operate both in a situated and the diasporic imaginary of South Asia. While the idea of the popular in South Asia has often been circumscribed by the spaces and cultural politics of Bollywood, this interdisciplinary volume takes an innovative turn to examine how academics, advocates, activists, and artists envision the inroads and consequences of nationalism, globalization and or empire, which continually remake communities and alter needs and allegiances. Through ethnography, literature, dance, cinema, activism, poetry, and storytelling, the authorsd analyse popular and social justice using a focused, multidisciplinary gendered lens. This book was originally published as a special issue of South Asian Popular Culture - publisher.
Includes bibliographical references and index.
Keywords: Feminism -- South Asia; Feminist theory -- South Asia; Women in popular culture -- South Asia